Comparative study of the psychometric properties of multiple-choice tests using confidence and number right scoring techniques - Jimoh Kasali; Adediwura Alaba Adeyemi (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2022)
Purpose - This study aims to ascertain the impact of several options on distractor performance when confidence scoring was used and established the impact of the numbers of options for multiple-choice test items on the reliability of coefficients that were not significant.Method: This research used a descriptive survey design. There are two sampling methods used in this research, simple random sampling technique and purposive sampling. The instrument used for this study was an adapted version of the 2015 West Africa School Certificate Examination (WASCE) Economics test items. Data collected were analyzed using ANOVA, Kuder -Richardson Formula (KR-20) and Fisher's Z-Test with aid of FZT compotator.Result - The results of the study showed that several options had a significant impact on distractors' performance when scored using confidence scoring (F = 6.679, p 0.05). The results also showed that for each pairwise comparison of 3/4-options (zobt = 0.640), 3/5-options (zobt = 0.837) and 4/5-options (zobt = 0.196) at p 0.05 the difference in the reliability coefficients were not significant.Implication - This study suggests to improve scoring, the procedure should be encouraged and used in schools because it is effective in reducing the contribution of random guessing to testees' total score and in rewarding testees' partial knowledge on multiple-choice tests. Furthermore, the confidence scoring procedure significantly reduces the 'craze' for a do-or-die affair to pass an examination at all costs and thus should be used in all schools.Originality - This research is the study to improve scoring procedures that should be encouraged and used in schools.***Tujuan - Tujuan dari penelitian ini adalah memastikan dampak jumlah opsi pada kinerja pengecoh ketika penilaian kepercayaan digunakan dan menetapkan dampak jumlah opsi untuk item tes pilihan ganda pada keandalan koefisien tidak signifikan.Metode - Penelitian ini menggunakan desain survei deskriptif. Ada dua metode pengambilan sampel yang digunakan dalam penelitian ini, yaitu teknik simple random sampling dan purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah versi adaptasi dari soal-soal tes Ekonomi West Africa School Certificate Examination (WASCE) 2015. Data yang terkumpul dianalisis menggunakan ANOVA, Rumus Kuder-Richardson (KR-20) dan Fisher's Z-Test dengan bantuan kompotator FZT.Hasil - Hasil penelitian menunjukkan bahwa jumlah opsi memiliki pengaruh yang signifikan terhadap kinerja pengecoh ketika diberi skor menggunakan penilaian kepercayaan (F = 6.679, p 0,05). Hasil juga menunjukkan bahwa untuk setiap perbandingan berpasangan opsi 3/4 (zobt = 0,640), opsi 3/5 (zobt = 0,837) dan opsi 4/5 (zobt = 0,196) pada p 0,05 selisih koefisien reliabilitas tidak signifikan.Implikasi - Penelitian ini menyarankan untuk meningkatkan prosedur penilaian harus didorong dan digunakan di sekolah-sekolah karena telah terbukti efektif dalam mengurangi kontribusi tebakan acak terhadap skor total testi dan dalam menghargai pengetahuan parsial testi pada tes pilihan ganda. Selanjutnya, prosedur penilaian kepercayaan secara signifikan mengurangi 'kegemaran' untuk urusan do-or-die untuk lulus ujian di semua biaya, dan dengan demikian harus digunakan di semua sekolah.Orisinalitas - Penelitian ini adalah studi untuk meningkatkan prosedur penilaian harus didorong dan digunakan di sekolah.